A Canadian Ethanol Feedstock Study to Benchmark the Relative Performance of Triticale: I. Agronomics. (1st November 2013) - Beres, Brian; Pozniak, Curtis; Eudes, Francois; Graf, Robert; Randhawa, Harpinder; Salmon, Don; McLeod, Grant; Dion, Yves; Irvine, Byron; Voldeng, Harvey; Martin, Richard; Pageau, Denis; et al.
Abstract : A need has been identified for alternative crop(s) with high grain yield, low grain protein concentration, and high starch for the ethanol industry. The objective of this study was to benchmark the relative performance of triticale (× Triticosecale ssp.) to wheat ( Triticum aestivum L.) classes currently utilized for ethanol production. Sixteen cultivars—three triticale, four Canada prairie spring (CPS) wheat, three Canada western soft white spring wheat (CWSWS), two Canada western red spring (CWRS) wheat, and four Canada western general purpose (CWGP) candidate cultivars—were grown at 36 locations across western Canada from 2006 to 2009. The performance of these cereal classes can generally be summarized as triticale = Hoffman (CWGP) = CWSWS > CPS white > CPS red > CWRS for most variables. The triticale and white wheats produced 12 and 13% more grain, respectively, than the hard red spring wheats. Among the triticales, AC Ultima's and Pronghorn's yield potential were most notable because they exceeded the CWRS cultivars AC Barrie and AC Superb by an average of 32% and the CPS red cultivars 5700PR and AC Crystal by 18%. The triticales and Hoffman matured later than most other cultivars. Pronghorn consistently displayed low levels of fusarium head blight (FHB), Septoria nodorum blotch, and powdery mildew, but elevated ergot levels were observed for all triticales. We conclude that triticale would be superior to CPS and CWRS wheat and similar to CWSWS in many agronomic traits desired by ethanol fermentation plants and is superior for biomass production.